2020
DOI: 10.1136/bmjopen-2019-031622
|View full text |Cite
|
Sign up to set email alerts
|

Characterising and predicting persistent high-cost utilisers in healthcare: a retrospective cohort study in Singapore

Abstract: ObjectiveWe aim to characterise persistent high utilisers (PHUs) of healthcare services, and correspondingly, transient high utilisers (THUs) and non-high utilisers (non-HUs) for comparison, to facilitate stratifying HUs for targeted intervention. Subsequently we apply machine learning algorithms to predict which HUs will persist as PHUs, to inform future trials testing the effectiveness of interventions in reducing healthcare utilisation in PHUs.Design and settingThis is a retrospective cohort study using adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In addition, an estimated 560,000 (18.6% prevalence) Singapore residents in 2015 have prediabetes, of whom an estimated 490,000 (16.2% prevalence) were undetected. Type 2 diabetes has been identified as a chronic disease whose patients persistently incur high health care costs [ 3 ]. Effective scalable prevention measures are thus urgently needed to prevent and better manage type 2 diabetes to reduce its burden.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an estimated 560,000 (18.6% prevalence) Singapore residents in 2015 have prediabetes, of whom an estimated 490,000 (16.2% prevalence) were undetected. Type 2 diabetes has been identified as a chronic disease whose patients persistently incur high health care costs [ 3 ]. Effective scalable prevention measures are thus urgently needed to prevent and better manage type 2 diabetes to reduce its burden.…”
Section: Introductionmentioning
confidence: 99%
“…For the topic of health care utilization and costs, 24 articles were included in this review. Most were retrospective cohort studies, 75 76 77 78 79 80 81 82 83 84 85 86 87 while six used prospective cohort studies, 88 89 90 91 92 93 four used a cross-sectional design, 94 95 96 97 and one used a survey for primary data collection. 98 Most studies used the EHR and administrative databases to collect data but three used surveys, 87 96 98 two used public datasets, 78 95 one used mobile phone data, 97 one used images, 90 and one used data from social media.…”
Section: Resultsmentioning
confidence: 99%
“…92 All studies were adult based with the exception of one study examining families. 98 Most studies were based in the United States, with the exception of three from Singapore, 83 85 93 one from China, 80 one from Brazil, 77 one from Italy, 88 one from Canada, 90 and one from the United Kingdom. 87 Sample sizes ranged from 190 to 780,295 observations.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some studies specifically focussed on patients with a temporary HNHC status such as Transient High Utilisers (THUs) in the study by Ng et al or cost bloomers in the study by Tamang et al Predicting temporary HNHC status may be particularly difficult but may also provide understanding in the difference between these two populations. 38,46 Model performance varied and was not always described in detail. Most studies (n = 45; 75%) conducted validation, yet this was external in only 20 studies (33%) limiting implications for clinical applicability.…”
Section: Discussionmentioning
confidence: 99%
“…2). 37,38 External validation of one of these models (HRUPoRT: High Resource User Population Risk Tool) in a separate study demonstrated strong discriminative ability (C-statistic 0.83) and good calibration (K in Fig. 2).…”
Section: Applicability For Clinical Usementioning
confidence: 99%